Click Coupling of Flavylium Dyes with Plasmodione Analogues: Towards New Redox‐Sensitive Pro‐Fluorophores - Dupouy, Baptiste; Cotos, Leandro; Binder, Annika; Slavikova, Lucie; Rottmann, Matthias; Mäser, Pascal; Jacquemin, Denis; Ganter, Markus; Davioud‐Charvet, Elisabeth; Elhabiri, Mourad (Chemistry – A European Journal, 2024)
Abstract